Junior Accounting Technician Training for the Business and Management Subject Teacher Forum (STWG) of Balikpapan - Wijayani, Dahyang Ika Leni; Kusno, Hendra Sanjaya; Finanto, Hasto (Journal of Applied Community Engagement, 2023)
The purpose of this community service project is to improve the business and management competencies of Balikpapan City vocational school instructors, with a focus on junior accounting technicians' abilities. The service team and partners have agreed upon priority concerns, which include aspects related to partner capabilities and information technology. Regarding partner capability, the challenges faced by partners are as follows: (1) there are very few teachers (one in every 50, or approximately 2% of teachers) who are certified in junior accounting technical competency; (2) teachers want to be able to graduate students from vocational schools who are capable of working as junior accounting technicians; and (3) there are no resources available to assist teachers in becoming certified in junior accounting technical competency. In order to address current issues, the following activity is provided as part of the community service: offline training to help prepare for the junior accounting technician competency exam. There are multiple steps involved in the implementation of this activity: (1) planning; (2) implementation; and (3) monitoring and assessment. Community service journals, mentorship materials, publishing in local mass media are the output targets to be met in this program.